Forming of composite spars including interlayers of aligned, multiwall, carbon nanotubes: An experimental study. Issue 1 (1st February 2016) - Hallander, P.; Sjölander, J.; Åkermo, M.
Abstract : Carbon nanotubes offer the potential for improved or changed matrix properties, thereby enabling the creation of novel, multifunctional composite materials. By using highly aligned, multiwall, carbon nanotubes (MWCNT) with thermoset resins, good dispersion and distribution of nanotubes is obtained. To date, research has mainly focused on improving the growth process of the aligned MWCNTs, however little has been done on the processing of composites that include MWCNTs as interlayers in the stack. The aim of this work is to study how the aligned MWCNTs are affected within composite part forming. The study shows that MWCNTs are influenced by the shearing that occurs during forming, but still maintain their integrity. To some extent, the shear pattern observed in the MWCNTs after deformation provides an indication of deformation modes. However, the presence of MWCNTs also significantly influences the forming characteristics of the prepreg stack. POLYM. COMPOS., 39:181–191, 2018. © 2016 Society of Plastics Engineers